Pandemic prevention via tourism: A conceptual framework. (September 2022) - Jiang, Yangyang; Wen, Jun; Zheng, Danni; Phau, Ian; Wang, Wei
Graphical abstract: Unlabelled Image Highlights: Present the status of research on the nexus between tourism and public health Explore how tourism has responded to pandemic prevention Discuss marketing strategies in post-COVID-19 tourism recovery Propose future research by integrating tourism, public health, and marketing fields